Continuity and change in diocese and province: the role of a Tudor bishop - Ayris, Paul (The historical journal, 1996)
Thomas Cranmer's register is important in shedding valuable shafts of light on the nature of the episcopal office in Tudor England. Despite the government's break with Rome in the 1530s, much of the archbishop's routine administration continued unaltered. Nonetheless, there were profound changes in Cranmer's role. Royal commissions, proclamations, injunctions, letters missive and acts of parliament all served to modify Cranmer's position as principal minister of the king's spiritual estate. When the crown issued a commission to the archbishop for the exercise of his jurisdiction, the prelate's position as a royal official was clear for all to see. It is sure, however, that the impact of Christian humanism and reformed theology also did much to shape Cranmer's work. The enforcement of the English Litany and, most notably, of the 42 Articles reveal the changing nature of the episcopal office at this time. In contrast to received orthodoxy, it is now clear that the bishops mounted a widespread campaign at the end of Edward VI's brief reign to secure use of this reformed formulary. There can be little doubt that Thomas Cranmer's years at Canterbury were of great significance in reshaping the role of the episcopate in early modern England.